OS2.1 Objective responses to chemotherapy in recurrent glioma do not predict better survival: A prospective analysis from the German Glioma Network. (19th September 2018) - Bähr, O; Hentschel, B; Hattingen, E; Reusche, M; Tatagiba, M; Tonn, J; Schnell, O; Schackert, G; Westphal, M; Herrlinger, U; Pietsch, T; Reifenberger, G; et al.
Abstract: Background: Outside of clinical trials, the occurrence of objective responses (OR) to chemotherapy in patients with recurrent gliomas is poorly characterized. Further, the predictive value of OR for progression-free survival (PFS) and overall survival (OS) in glioma patients is unclear. Material and Methods: We screened the German Glioma Network Database for patients who had received any chemotherapy for recurrent glioma from 2004–2008. Patients with a prior gross total resection of the recurrent tumor, patients receiving additional radiotherapy for the recurrent tumor and patients with spinal gliomas were excluded. As PFS was not available for a large number of patients we used the composite endpoint time-to-treatment-failure (progressive disease, start of a new therapy or death). Results: We included 485 patients who received 646 chemotherapy regimens for treatment of recurrent glioma. Of these, only 32 chemotherapies in 32 patients resulted in an objective response (30 PR, 2 CR) after central neuroradiological review according to RANO criteria. OR rates were 2.8%, 11.0% and 10.6% for glioblastoma, anaplastic glioma WHO grade III and diffuse glioma WHO grade II, respectively. Temozolomide (n=232) resulted in ORs in 7.8% of the patients, while nitrosourea (n=212) and imatinib (n=27) resulted in ORs in 6.1% and 3.7%, respectively. Overall, responders showed a significantly improved OS compared to non-responders (median OS 33.3 versus 15 months, p=0.054). Yet, a Cox regression analysis adjusted for diagnosis (including WHO grade) and age did not reveal a significant association of objective responses with overall survival (relative risk 0.8, p=0.391). In addition, we generated a 1:3 cohort (n=96) of non-responders matched for histology and WHO grade. There was no relevant difference in OS comparing responders to the matched cohort (median OS 33.3 versus 25.6 months, p=0.929). When comparing non-responders with longer time-to-treatment-failure (>14 weeks, assumed stable disease as best response) with responders (n=32) the difference in outcome was lost (median OS 24.3 versus 33.3 months, p=0.86). In contrast, non-responders with shorter time-to-treatment-failure (<14 weeks, assumed progressive disease as best response) had dramatically shorter survival (median OS 6.4 versus 33.3 months, p<0.05). Conclusion: In this large, prospective study objective responses to chemotherapy in the recurrent setting were rare in glioma patients. Notably, when comparing responders with a matched cohort or patients with assumed stable disease as best response, objective responses do not seem to be associated with improved survival.